Occurrence of bisphenol S in the environment and implications for human exposure: A short review - Wu, Liu-Hong; Zhang, Xue-Mei; Wang, Fei; Gao, Chong-Jing; Chen, Da; Palumbo, Jillian R.; Guo, Ying; Zeng, Eddy Y. (The Science of the total environment, 2018)
As a substitute of bisphenol A (BPA), bisphenol S (BPS) has been applied in consumer products present in our daily lives. With a similar chemical structure as BPA, BPS has also been demonstrated as an exogenous endocrine disrupting chemical. Compared with a large number of studies on BPA, investigation on BPS has remained limited. In this study, we reviewed the literature of BPS mainly published during 2010–2017, including its environmental distributions, toxicities, and human exposure. The data demonstrated that BPS is now ubiquitous in the environment and found worldwide, but generally with concentration levels lower than BPA in various environment media, including water, sediment, sludge, indoor dust and air, consumer products, and human urine. However, we found that the concentration levels of BPS in aquatic environments, especially water samples, were almost comparable or equal to that of BPA. Our summary also indicated that process speed of substituting BPA with BPS in consumer products in the U.S. was relatively faster than other countries. In addition, we summarized the toxicities of exposure to BPS both in vivo and in vitro experiments. The current data supports that exposure to BPS may have adverse effects on reproductive systems, endocrine systems, and nervous systems in animals and humans, and may trigger oxidative stress. The occurrence of BPS was frequently reported in human urine, but rarely in other human samples. The current research indicates that food is the dominant source for human exposure to BPS, and the contribution of personal care product usage is low. The occurrence of BPS and their metabolites in the human body and the guidelines for BPS exposure merit further investigation. [Display omitted] •BPA was gradually substituted by BPS in consumer products worldwide.•The concentration ratios of BPS to BPA were higher in the aquatic environment than in other environmental media.•Food is the dominant source for general population exposure to BPS.